Mapping of a QTL associated with sucrose content in peanut kernels using BSA-seq - Guo, Junjia; Qi, Feiyan; Qin, Li; Zhang, Maoning; Sun, Ziqi; Li, Hongyan; Cui, Mengjie; Zhang, Mengyuan; Li, Chenyu; Li, Xiaona; Zhao, Qi; Luo, Dandan; et al. (Frontiers in Genetics, 2023)
As an important factor affecting the edible quality of peanut kernels, sucrose content is a complex quantitative trait regulated by multiple factors. In this study, an F2 segregating population and a recombinant inbred line (RIL) population, derived from a cross between the high sucrose content variety Jihuatian 1 and the low sucrose content line PI478819, were used as materials to map a quantitative trait locus (QTL) associated with sucrose content in peanut kernels. Four QTLs were initially located on chromosomes A03 and A06 based on BSA-seq technology, and multiple kompetitive allele-specific PCR markers were developed based on single-nucleotide polymorphisms (SNPs) in the intervals. The markers were genotyped in the RIL population and finely mapped to a stable QTL, qSUCA06, located on chromosome A06 within a 0.29-Mb physical genomic interval (112367085–112662675 bp), which accounted for 31.95%–41.05% of the phenotypic variance explained. SNP and insertion/deletion annotations were performed on genes in the candidate interval, and having screened out those genes with mutations in exons, candidate genes were verified by qRT-PCR. The results revealed that Arahy.Y2LWD9 may be the main gene regulating sucrose content. The QTL identified in this study will not only contribute to marker-assisted breeding for improvement of peanut sucrose content but also paves the way for identifying gene function.